Future directions for radiotherapy: GRAY or BLUE perspective? - Maciejewski, Bogusław (Contemporary Oncology/Współczesna Onkologia, 2000)
Over the past 20 years radiobiological and clinical rationale for altered radiotherapy were defined. Better understanding of the importance of dose per fraction, overall treatment time, time interval between fractions, and tumour and normal tissue repair mechanisms have contributed to the studies on accelerated (AF) and hyperfractionated (HF) radiotherapy. The results of these studies lead to development of combined AF-HF schedules. Amoung numerous pilot and randomized studies the only few were recognized as important. Hyperfractionation was found to be advantegeous in advanced oropharyngeal cancers, and CHART increased therapeutic gain in advanced laryngeal cance. Accelerated hyperfractionation (AF-FH) improves local control and/or permits a lower total dose for the same rate pf control. Better tumour control has always involved increased severity of acute mucosal reactions. The results of clinical trials which improved effectiveness of radiotherapy are discussed. A variety of physical parameters used in altered fractionation makes difficult the comparison of biological effect of different fractionation regimens based on doses in Grays. A new concept of Biological Unit of Effectiveness – BLUE, proposed by Withers is presented. It is interesting complex system of biological dosimetry which might supplement the Gray doses. Basic assumption of this concept and practical example are presented.